Analysis of the Implementation of the Government Financial Accounting System in Improving the Quality of Regional Government Financial Reports (Case Study at the Sunggal Sub-District Office, Deli Serdang Regency) - Ritonga, Jukhairia; Siregar, Saparuddin; Ilhamy Nasution , Muhammad Lathief (Journal of Management, Economic, and Accounting, 2023)
This study seeks to determine how the use of the government financial accounting system affects the caliber of local government financial reports in the Sunggal District Office, Deli Serdang Regency,. This study employs a qualitative descriptive methodology and uses interviewing and documenting as data collecting approaches. According to the study's findings, the Sunggal District Office in the Deli Serdang Regency might benefit from the installation of a government financial accounting system by producing better financial reports.